A Bloom Filter Based Model for Decentralized Authorization. Issue 6 (26th March 2013) - Foley, Simon N.; Navarro‐Arribas, Guillermo
<x xml:space="preserve">Abstract</x> A decentralized authorization mechanism is proposed that uses Bloom filters to implement authorization delegation. This lightweight mechanism is unlike conventional approaches that typically rely on public key certificates to implement distributed delegation. In taking an approach based on one‐way hash functions, the mechanism may be preferable for use in computationally constrained environments where public‐key cryptography is not desirable.